Penerapan Pendekatan Inkuiri untuk Meningkatkan Berpikir Kritis PAI di Kelas 8 SMPN 1 Sawahan - Lilik Hanifah (P-SEMART JOURNAL, 2022)
This study aims to evaluate the influence of implementing an inquiry-based approach on students’ critical thinking skills in the subject of Pendidikan Agama Islam in 8th grade at SMP Negeri 1 Sawahan Madiun. The research utilized the Classroom Action Research (CAR) method. The study was conducted through several cycles, including planning, implementation, observation, and reflection. Data were collected through classroom observations, critical thinking ability tests, and interviews with students. The results of the study indicated that the implementation of the inquiry-based approach significantly improved students’ critical thinking skills. Students demonstrated improvements in their ability to analyze, evaluate, and connect religious concepts with everyday life contexts. They also actively engaged in the learning process and exhibited a high level of interest in Pendidikan Agama Islam. The study concluded that the implementation of the inquiry-based approach has the potential to enhance students’ critical thinking skills in the subject of Pendidikan Agama Islam. Recommendations from this study include integrating the inquiry-based approach into the teaching of Pendidikan Agama Islam in 8th grade at SMP Negeri 1 Sawahan Madiun, as well as providing training for teachers on effective strategies and techniques for implementing this approach.